IMPLEMENTASI MUTUAL LEGAL ASSISTANCE (MLA) DIINDONESIA TERHADAP PENYELESAIAN KEJAHATAN YANGDIATUR DALAM UNITED NATIONS CONVENTION AGAINSTTRANSNATIONAL ORGANIZED CRIME (UNTOC) - Aulia Dama Gucci (2020)
Transnational crime or transnational crosscountry crimes was seen as one of a serious threat to global security it seeks to under domestic laws or national jurisdiction, not being under judicial jurisdiction by international community for it's one of the constituents of cross-border transnational is that there is a Mutual Legal Assistance. Usually in the collection and the submission of evidence that done by one authority or law enforcement from one country to authority or law enforcement in other countries, in response to request for assistance. The implementation of Mutual Legal Assistance for of crimes arranged in United Nations Convention Against Transnational Organized Crimes evidence, concerned with the collection service to, related documents, seizure identifying and tracking, as well as to facilitate the presence of the person. United Nations Convention Against Transnational Organized Crimes is the conventions that are held with the aim to eredice transnational crime under the bilateral cooperation, multilateral and international. United Nations Convention Against Transnational Organized Crimes set six transnational crime, is corruption, money laundering, trade women and children smuggling, arms smuggling, and obstructing judicial process. The implementation of Mutual Legal Assistance when is felt to be not very effective liaison and the handling of transnational crime, the implementation process an application and assistance are arranged in an Indonesian Law Number 1 The year of 2006 about mutual legal assistance in trouble seen the criminal of procedure delays and eating cost. It is hoped the perfection will be least the law against constitution to make it more effective.